2006
DOI: 10.5194/acp-6-1895-2006
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diurnal characteristics of water soluble inorganic compounds in the gas and aerosol phase in the Zurich area

Abstract: Abstract. Gas and aerosol samples were taken using a wet effluent diffusion denuder/aerosol collector (WEDD/AC) coupled to ion chromatography (IC) in the city of Zurich, Switzerland from August to September 2002 and in March 2003. The water soluble inorganic anions nitrate, sulfate, and nitrite were analyzed online with a time resolution of two hours for the gas and aerosol phase. The fraction of water soluble inorganic anions in PM10 varied from 15% in August to about 38% in March. Seasonal and diurnal variat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 45 publications
5
19
2
Order By: Relevance
“…These diurnal cycles resemble those observed at other sites, for instance Zürich (Fisseha et al, 2006), Pittsburgh (Wittig et al, 2004), and Oensingen, Switzerland (Wolff et al, 2010): the peak nitrate concentration is a few hours earlier than that of HNO 3 . The time lag can be explained by the temperature dependent partitioning of ammonium nitrate between the gas and aerosol phase (e.g., Fisseha et al, 2006). The times of the diurnal maxima are not quite the same at the sites.…”
Section: Hno 3 and Hnosupporting
confidence: 58%
See 3 more Smart Citations
“…These diurnal cycles resemble those observed at other sites, for instance Zürich (Fisseha et al, 2006), Pittsburgh (Wittig et al, 2004), and Oensingen, Switzerland (Wolff et al, 2010): the peak nitrate concentration is a few hours earlier than that of HNO 3 . The time lag can be explained by the temperature dependent partitioning of ammonium nitrate between the gas and aerosol phase (e.g., Fisseha et al, 2006). The times of the diurnal maxima are not quite the same at the sites.…”
Section: Hno 3 and Hnosupporting
confidence: 58%
“…For example, in Oensingen in the late summer of 2006, the maximum HNO 3 concentration was clearly later in the afternoon (16:00-17:00) (Wolff et al, 2010), which is about 4 h later than in our spring period in Helsinki. In our study the HNO 3 concentration decreased in the afternoon, probably due to dry deposition and heterogeneous formation of nitrate, as suggested for example by Fisseha et al (2006) for the similar cycle in Zürich. The day-to day variation of HNO 3 was large in our data, which is due to variation in both sources and removal.…”
Section: Hno 3 and Hnosupporting
confidence: 50%
See 2 more Smart Citations
“…We have found that the thermodynamic equilibrium module produces a too stable ammonium nitrate in winter and during night time in summer, whereas during the daytime in summer it is too unstable. Earlier studies have also identified an underestimation of the particulate nitrate concentrations during summer and daytime (Moya et al, 2001;Fisseha et al, 2006;Morino et al, 2006). In contrast, a number of studies have shown that the predicted equilibrium is generally in accordance with observations (Zhang et al, 2003;Takahama et al, 2004;Yu et al, 2005), though also in these studies significant discrepancies between measured and predicted partitioning have been observed.…”
Section: Discussioncontrasting
confidence: 38%